SMART AND HUMANITARIAN ASPECTS OF TEACHING IN HIGHER EDUCATION - Anatoly V. Zavrazhin (Статистика и экономика)
The article deals with humanization and humanization the higher education systemin Russia, reveals its purpose and content,features implementation in the context ofimplementing SMART education on the example of MESI.